Enhancing Classroom Interaction Through Teacher Questioning Strategies: An Analysis of Question Types and Student Engagement in EFL Learning - Rahmaeni Rahmaeni (Majesty Journal, 2025)
Teacher questioning plays a crucial role in shaping student engagement and learning outcomes in English as a Foreign Language (EFL) classrooms. However, previous research indicates that many EFL teachers predominantly use display questions, which limit students' opportunities for critical thinking and communicative competence. This study investigates the types of questions employed by teachers in an EFL classroom at SMAN 3 Enrekang and examines their impact on student participation. Using a qualitative descriptive approach, data were collected through classroom observations and video recordings, which were analyzed using Miles and Huberman’s interactive model. The findings reveal that display questions were the most frequently used, followed by yes/no, referential, and open-ended questions. While display questions effectively assess comprehension, they often elicit brief, factual responses rather than promoting in-depth discussion. In contrast, referential and open-ended questions, though less frequent, encourage longer, more meaningful student responses, fostering higher-order thinking. Challenges such as curriculum constraints, student language proficiency, and teacher questioning habits contribute to the limited use of diverse questioning strategies. These findings suggest that EFL teachers should adopt a more balanced approach to questioning, incorporating both lower-order and higher-order questions to enhance classroom interaction. The study highlights the need for teacher training programs to equip educators with effective questioning techniques and recommends further research on the long-term impact of questioning strategies on language acquisition. By refining classroom discourse, this study contributes to improving pedagogical practices and fostering active student participation in EFL learning environments.